2009
DOI: 10.1039/b9pp00053d
|View full text |Cite
|
Sign up to set email alerts
|

Pyrearinus termitilluminans larval click beetle luciferase: active site properties, structure and function relationships and comparison with other beetle luciferases

Abstract: Several beetle luciferases have been cloned and sequenced. However, most studies on structure and function relationships and bioanalytical applications were done with firefly luciferases, which are pH sensitive. Several years ago we cloned Pyrearinus termitilluminans larval click beetle luciferase, which displays the most blue-shifted bioluminescence among beetle luciferases and is pH insensitive. This enzyme was expressed in E. coli, purified, and its properties investigated. This luciferase shows slower lumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Therefore, these kinetic properties may not contributed to the high light output of ELuc in living cells. In contrast, the decay constant of the luminescence of the wild-type luciferase is higher than that of FLuc [6]. When we measured the luminescence kinetics of purified FLuc protein by adding ATP and Mg 2+ as cofactors and D-luciferin, the luminescence displayed flash-like kinetics (Figure 1E), as descried previously [10].…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Therefore, these kinetic properties may not contributed to the high light output of ELuc in living cells. In contrast, the decay constant of the luminescence of the wild-type luciferase is higher than that of FLuc [6]. When we measured the luminescence kinetics of purified FLuc protein by adding ATP and Mg 2+ as cofactors and D-luciferin, the luminescence displayed flash-like kinetics (Figure 1E), as descried previously [10].…”
Section: Resultssupporting
confidence: 74%
“…The sustaining luminescence kinetics of FLuc are partly attributed to coenzyme A (CoA), a vestigial substrate of beetle luciferase included with the PicaGene reagent, by which CoA removes from the FLuc active site the inhibitors that are produced by luciferin–luciferase reaction [15], [16]. Similarly, CoA also seems to participate in the long-lasting light production of ELuc, as discussed by Silva Neto et al [6]. In contrast to the light output from living cells, the resulting bioluminescence intensity of purified ELuc protein (normalized to the amount of protein) was unexpectedly slightly lower than that of FLuc, (Figure S3B), suggesting that the brighter luminescent signal from viable cells is not simply attributable to the enzymatic activity of the lucifearase.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Comparing the K M values for luciferin and ATP of the wild‐type luciferases and the half‐life (Table ) we found that P . termitilluminans , which shows the highest thermostability, displayed high values of K M for ATP and luciferin . Similarly, P. vivianii green‐emitting luciferase, which is the most stable among railroad worm luciferases, also showed high K M values for both substrates, especially for luciferin which was one of the highest reported for beetle luciferases.…”
Section: Resultsmentioning
confidence: 99%